Atomic layer deposition coated phosphorus-carbon negative electrode material and preparation method and application thereof
By depositing and covering the Al2O3 layer on the surface of the phosphorus-carbon composite material, the problems of structural instability and air sensitivity of the negative electrode material of the sodium ion battery are solved, and higher cycle stability and storage time are achieved.
Patent Information
- Application Number
- CN202411643982.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
The existing sodium ion battery anode materials have unstable structural structure and air sensitivity during circulation, resulting in degradation and deterioration of performance.
Through atomic layer deposition technology, Al2O3 layer is coated on the surface of the phosphorus carbon composite to form a PC@Al2O3 composite material, improving its circulation stability and air corrosion resistance.
The cycle stability and storage time of phosphorus-carbon composites in sodium ion batteries are significantly improved, the problems of volume expansion and air sensitivity are solved, and the efficient electrochemical performance is maintained.
Smart Images

Figure CN119480998A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to an atomic layer deposition coated phosphorus-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have become one of the most competitive electrochemical energy storage technologies due to their rich sodium storage capacity and low price. However, commercial graphite anodes cannot be used in sodium-ion batteries due to their low sodium storage capacity, so there is an urgent need to find a suitable sodium-ion battery anode. Among them, hard carbon materials have excellent performance in sodium-ion batteries due to their rich defect sites, developed pore structure and large interlayer spacing. However, the gram capacity of most commercial hard carbon materials is less than 300 mAh g -1 , which seriously hinders the further development of sodium-ion batteries.
[0003] Red phosphorus as anode material for sodium-ion batteries can provide 2596 mAh g -1 The gram capacity of red phosphorus is 2.5777 W / m, but the poor conductivity of red phosphorus and its large volume expansion during the cycle limit its use in sodium-ion batteries. To solve this problem, researchers combined phosphorus and carbon to prepare phosphorus-carbon composites, using the synergistic effect of phosphorus-based and carbon materials to achieve higher energy density and better rate performance. However, phosphorus-carbon composites have problems with structural instability and air sensitivity during the cycle. When placed in the air, they are easily reacted with oxygen and moisture in the air to form phosphoric acid on the surface. Then, phosphorus, carbon, and phosphoric acid will form micro-batteries on the surface of the composite material, which will further cause the composite material to deteriorate. This phenomenon limits its further development and needs to be solved urgently. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned prior art, the present invention provides an atomic layer deposition coated phosphorus-carbon negative electrode material and a preparation method and application thereof, and improves its cycle stability in sodium ion batteries by atomic layer deposition coating on the surface of the phosphorus-carbon composite material.
[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0006] In a first aspect, the present invention provides an atomic layer deposition coated phosphorus-carbon negative electrode material, comprising Al 2 O 3 , red phosphorus and activated carbon, wherein the red phosphorus is supported on the surface of the activated carbon, and the Al 2 O 3 Coated on the surface of red phosphorus.
[0007] Preferably, the Al 2 O 3The precursor materials are trimethylaluminum and water.
[0008] The atomic layer deposition coated phosphorus-carbon negative electrode material provided by the present invention has excellent electrochemical performance. The present invention uses trimethylaluminum and water as precursors to uniformly deposit Al on the surface of the phosphorus-carbon composite to obtain 2 O 3 Coated phosphorus-carbon composite material; the coating layer Al of the present invention 2 O 3 It has high uniformity and density, ensuring the mechanical strength of the composite; in addition, the coating layer Al 2 O 3 It can also be used as an artificial SEI (solid electrolyte interface) for composite electrodes to produce a stable electrode / electrolyte interface, further improving the structural stability and cycle performance of phosphorus-carbon composites as negative electrode materials for sodium-ion batteries.
[0009] Preferably, the mass ratio of red phosphorus to activated carbon is (50~45):(50~55).
[0010] In a second aspect, the present invention provides a method for preparing an atomic layer deposition coated phosphorus-carbon composite material, comprising the following steps:
[0011] S1. Loading red phosphorus on activated carbon to prepare phosphorus-carbon composite (PC);
[0012] S2, the coating precursor material is loaded on the phosphorus-carbon composite by atomic layer deposition to obtain an atomic layer deposition coated phosphorus-carbon composite material (PC@Al 2 O 3 ).
[0013] Preferably, the preparation process of the phosphorus-carbon composite is as follows: red phosphorus and activated carbon are mixed in proportion and then dried to obtain a red phosphorus activated carbon precursor material; the red phosphorus activated carbon precursor material is transferred to a closed container, heated to sublime the red phosphorus, the sublimation temperature is 450~500℃, cooled to 200~300℃, then heated to 350℃ again, and finally cooled to obtain the phosphorus-carbon composite.
[0014] Preferably, the working temperature of the atomic layer deposition is 200°C, and the temperature of the delivery pipe is maintained at 90°C.
[0015] In a third aspect, the present invention provides an application of the atomic layer deposition coated phosphorus-carbon composite material or the atomic layer deposition coated phosphorus-carbon composite material prepared by the method in the negative electrode of a sodium ion battery.
[0016] In a fourth aspect, the present invention provides a negative electrode material for a sodium ion battery, wherein the raw material thereof includes the atomic layer deposition coated phosphorus-carbon composite material, or includes the atomic layer deposition coated phosphorus-carbon composite material prepared by the preparation method.
[0017] Preferably, the raw materials of the negative electrode material further include a conductive agent and a binder.
[0018] Compared with the prior art, the present invention is beneficial in that:
[0019] The atomic layer deposition coated phosphorus-carbon composite material provided by the present invention has good cycle stability. When applied to a sodium ion battery, the capacity retention rate of the obtained battery after 200 cycles at 0.2 A / g is 95%, which solves the problem that red phosphorus as the negative electrode of the sodium ion battery has excessive volume change during the charge and discharge process; In addition, the PC@Al 2 O 3 After 12 months of storage, the capacity retention rate of the composite material was still 93.6%, which was comparable to that before storage, thus solving the problem of phosphorus-carbon composites being sensitive to air. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 For PC@Al 2 O 3 TEM image of -30;
[0021] Figure 2 For PC@Al 2 O 3 -30 and PC-1 cycle performance comparison chart;
[0022] Figure 3 For PC@Al 2 O 3 -30 and PC@Al 2 O 3 -30-12 month cycle performance comparison chart. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The present invention provides an atomic layer deposition coated phosphorus-carbon negative electrode material, comprising Al 2 O 3 , red phosphorus and activated carbon, wherein the red phosphorus is supported on the surface of the activated carbon, and the Al 2 O 3 Coated on the surface of red phosphorus.
[0025] The Al 2 O 3 The precursor materials are trimethylaluminum and water.
[0026] In some examples, the mass ratio of red phosphorus to activated carbon is (50~45):(50~55).
[0027] The method for preparing the atomic layer deposition coated phosphorus-carbon composite material comprises the following steps:
[0028] S1. Loading red phosphorus on activated carbon to prepare phosphorus-carbon composite (PC);
[0029] S2. Put the phosphorus-carbon composite on an aluminum alloy disk and fix it with a stainless steel mesh disk to prevent the sample from leaking, and then perform vacuum treatment; use trimethylaluminum and water as precursors and use the atomic layer deposition method to load the coating precursor material on the phosphorus-carbon composite to obtain the atomic layer deposition coated phosphorus-carbon composite material (PC@Al 2 O 3 ).
[0030] Example 1
[0031] An atomic layer deposition coated phosphorus-carbon negative electrode material, the preparation steps are as follows:
[0032] (1) 50 g of red phosphorus and 50 g of activated carbon were mixed, ground, and dried at 80 °C for 6 h to obtain a red phosphorus-activated carbon precursor material;
[0033] (2) The red phosphorus-activated carbon precursor material was transferred to a stainless steel reactor. The reactor was evacuated and heated at 2 °C min -1 The temperature was raised to 500 °C at a rate of 2 °C·min -1 The temperature was cooled to 300 °C at a rate of 5 °C·min -1 The temperature was raised to 350 °C at a heating rate of 1.5 °C, kept at this temperature for 2 h, and finally cooled to room temperature to obtain a phosphorus-carbon composite in which red phosphorus was loaded in the pores of activated carbon.
[0034] (3) placing the phosphorus-carbon composite on an aluminum alloy disc and fixing it with a stainless steel mesh disc to prevent leakage of the sample, and then performing a vacuum treatment;
[0035] (4) Trimethylaluminum was introduced into the atomic deposition chamber with a 25 ms pulse. After 15 s of reaction, N 2 To remove unreacted trimethylaluminum, deionized water was introduced with a 15 ms pulse and N 2Remove the unreacted deionized water; repeat this step for 30 cycles to obtain the atomic layer deposition coated phosphorus-carbon negative electrode material, denoted as PC@Al 2 O 3 -30. PC@Al 2 O 3 -30 TEM image Figure 1 As shown in the figure, it can be seen that Al 2 O 3 Uniformly coated on the surface of the phosphorus / carbon composite.
[0036] (5) PC@Al obtained in step (4) 2 O 3 -30 was placed at room temperature for 12 months to obtain PC@Al 2 O 3 -30-Dec.
[0037] Example 2
[0038] An atomic layer deposition coated phosphorus-carbon negative electrode material, the preparation steps are as follows:
[0039] (1) 50 g of red phosphorus and 50 g of activated carbon were mixed, ground, and dried at 80 °C for 6 h to obtain a red phosphorus-activated carbon precursor material;
[0040] (2) The red phosphorus-activated carbon precursor material was transferred to a stainless steel reactor. The reactor was evacuated and heated at 2 °C min -1 The temperature was raised to 500 °C at a rate of 2 °C·min -1 The temperature was cooled to 300 °C at a rate of 5 °C·min -1 The temperature was raised to 350 °C at a heating rate of 1.5 °C, kept at this temperature for 2 h, and finally cooled to room temperature to obtain a phosphorus-carbon composite in which red phosphorus was loaded in the pores of activated carbon.
[0041] (3) placing the phosphorus-carbon composite on an aluminum alloy disc and fixing it with a stainless steel mesh disc to prevent leakage of the sample, and then performing a vacuum treatment;
[0042] (4) Trimethylaluminum was introduced into the atomic deposition chamber with a 25 ms pulse. After 15 s of reaction, N 2 To remove unreacted trimethylaluminum, deionized water was introduced with a 15 ms pulse and N 2 Remove the unreacted deionized water; repeat this step for 20 cycles to obtain the atomic layer deposition coated phosphorus-carbon negative electrode material, denoted as PC@Al 2 O 3 -20.
[0043] Example 3
[0044] An atomic layer deposition coated phosphorus-carbon negative electrode material, the preparation steps are as follows:
[0045] (1) 50 g of red phosphorus and 50 g of activated carbon were mixed, ground, and dried at 80 °C for 6 h to obtain a red phosphorus-activated carbon precursor material;
[0046] (2) The red phosphorus-activated carbon precursor material was transferred to a stainless steel reactor. The reactor was evacuated and heated at 2 °C min -1 The temperature was raised to 500 °C at a rate of 2 °C·min -1 The temperature was cooled to 300 °C at a rate of 5 °C·min -1 The temperature was raised to 350 °C at a heating rate of 1.5 °C, kept at this temperature for 2 h, and finally cooled to room temperature to obtain a phosphorus-carbon composite in which red phosphorus was loaded in the pores of activated carbon.
[0047] (3) placing the phosphorus-carbon composite on an aluminum alloy disc and fixing it with a stainless steel mesh disc to prevent leakage of the sample, and then performing a vacuum treatment;
[0048] (4) Trimethylaluminum was introduced into the atomic deposition chamber with a 25 ms pulse. After 15 s of reaction, N 2 To remove unreacted trimethylaluminum, deionized water was introduced with a 15 ms pulse and N 2 Remove the unreacted deionized water; repeat this step for 40 cycles to obtain the atomic layer deposition coated phosphorus-carbon negative electrode material, denoted as PC@Al 2 O 3 -40.
[0049] Comparative Example 1
[0050] A red phosphorus activated carbon composite material, the preparation steps are as follows:
[0051] (1) 50 g of red phosphorus and 50 g of activated carbon were mixed, ground, and dried at 80 °C for 6 h to obtain a red phosphorus-activated carbon precursor material;
[0052] (2) The red phosphorus-activated carbon precursor material was transferred to a stainless steel reactor. The reactor was evacuated and heated at 2 °C min -1 The temperature was raised to 500 °C at a rate of 2 °C·min -1 The temperature was cooled to 300 °C at a rate of 5 °C·min -1 The temperature was raised to 350 °C at a heating rate of 1.5 °C and kept at that temperature for 2 h. Finally, the mixture was cooled to room temperature to obtain a phosphorus-carbon composite in which active red phosphorus was loaded in the pores of activated carbon, which was recorded as PC-1.
[0053] Comparative Example 2
[0054] A red phosphorus activated carbon composite material, the preparation steps are as follows:
[0055] (1) 45 g of red phosphorus and 55 g of activated carbon were mixed, ground, and dried at 80 °C for 6 h to obtain a red phosphorus-activated carbon precursor material;
[0056] (2) The red phosphorus-activated carbon precursor material was transferred to a stainless steel reactor. The reactor was evacuated and heated at 2 °C min -1 The temperature was raised to 500 °C at a rate of 2 °C·min -1 The temperature was cooled to 300 °C at a rate of 5 °C·min -1 The temperature was raised to 350 °C at a heating rate of 1.5 °C and kept at that temperature for 2 h. Finally, the mixture was cooled to room temperature to obtain a phosphorus-carbon composite in which active red phosphorus was loaded in the pores of activated carbon, which was recorded as PC-2.
[0057] Comparative Example 3
[0058] An atomic layer deposition coated phosphorus-carbon negative electrode material, the preparation steps are as follows:
[0059] (1) 50 g of red phosphorus and 50 g of activated carbon were mixed, ground, and dried at 80 °C for 6 h to obtain a red phosphorus-activated carbon precursor material;
[0060] (2) The red phosphorus-activated carbon precursor material was transferred to a stainless steel reactor. The reactor was evacuated and heated at 2 °C min -1 The temperature was raised to 500 °C at a rate of 2 °C·min -1 The temperature was cooled to 300 °C at a rate of 5 °C·min -1 The temperature was raised to 350 °C at a heating rate of 1.5 °C, kept at this temperature for 2 h, and finally cooled to room temperature to obtain a phosphorus-carbon composite in which red phosphorus was loaded in the pores of activated carbon.
[0061] (3) placing the phosphorus-carbon composite on an aluminum alloy disc and fixing it with a stainless steel mesh disc to prevent leakage of the sample, and then performing a vacuum treatment;
[0062] (4) The operating temperature of the atomic layer deposition chamber was controlled at 200 °C, the temperature of the delivery tube was maintained at 90 °C, and tetrakis(dimethylamino)titanium was introduced into the atomic layer deposition chamber with a pulse of 25 ms. After reacting for 15 s, N 2 To remove unreacted tetrakis(dimethylamino)titanium, deionized water was introduced with a 15 ms pulse and N 2 Remove the unreacted deionized water; repeat this step for 30 cycles to obtain the atomic layer deposition coated phosphorus-carbon negative electrode material, denoted as PC@TiO 2-30.
[0063] Comparative Example 4
[0064] An atomic layer deposition coated phosphorus-carbon negative electrode material, the preparation steps are as follows:
[0065] (1) 50 g of red phosphorus and 50 g of activated carbon were mixed, ground, and dried at 80 °C for 6 h to obtain a red phosphorus-activated carbon precursor material;
[0066] (2) The red phosphorus-activated carbon precursor material was transferred to a stainless steel reactor. The reactor was evacuated and heated at 2 °C min -1 The temperature was raised to 500 °C at a rate of 2 °C·min -1 The temperature was cooled to 300 °C at a rate of 5 °C·min -1 The temperature was raised to 350 °C at a heating rate of 1.5 °C, kept at this temperature for 2 h, and finally cooled to room temperature to obtain a phosphorus-carbon composite in which red phosphorus was loaded in the pores of activated carbon.
[0067] (3) placing the phosphorus-carbon composite on an aluminum alloy disc and fixing it with a stainless steel mesh disc to prevent leakage of the sample, and then performing a vacuum treatment;
[0068] (4) The operating temperature of the atomic layer deposition chamber was controlled at 200 °C, the temperature of the delivery pipe was maintained at 90 °C, and diethyl zinc was introduced into the atomic layer deposition chamber with a pulse of 25 ms. After reacting for 15 s, N 2 To remove unreacted diethylzinc, deionized water was introduced with a 15 ms pulse and N 2 Remove the unreacted deionized water; repeat this step for 30 cycles to obtain an atomic layer deposition coated phosphorus-carbon negative electrode material, denoted as PC@ZnO-30.
[0069] The negative electrode materials prepared in Example 1 and Comparative Examples 1 to 6 were respectively applied to the negative electrode of button-type sodium ion batteries. The button-type half-cells assembled using Example 1 and Comparative Examples 1 to 6 were: A1 (PC@Al 2 O 3 -30), A2 (PC@Al 2 O 3 -30-12 months), A3 (PC@Al 2 O 3 -20)、A4(PC@Al 2 O 3 -40), B1 (PC-1), B2 (PC-2), B3 (PC@TiO 2-30), B4 (PC@ZnO-30). The battery preparation method is as follows: weigh the negative electrode material, conductive agent, and binder in a ratio of 90:3:7, stir the three to prepare a slurry, apply it on a copper foil, dry it, and press it to obtain the battery negative electrode; wherein the conductive agent is SP and single-walled carbon nanotubes; the binder is CMC. The electrolyte is NaPF 6 / EC+DEC (volume ratio 1:1, concentration 1 mol / L), metal sodium as the counter electrode, glass fiber membrane as the separator, button sodium ion battery assembled in a glove box filled with argon, electrochemical performance was tested on Wuhan Blue Electric CT2001A battery tester, voltage range 0.001-2 V, first cycle charge and discharge rate 0.1A / g, cycle charge and discharge rate 0.2 A / g. Test results are shown in Table 1, cycle performance results of A1, B1, B3 and B4 are shown in Figure 2 , the cycle performance results of A1 and A2 are shown in Figure 3 .
[0070] Table 1: Electrochemical performance of Example 1 and Comparative Examples 1 to 6
[0071]
[0072] From Table 1, we can see that A1, A3 and A4 all show high first coulombic efficiency and charge capacity, and the first coulombic efficiency and charge capacity of A2 are very close to those of A1; while the first coulombic efficiency and charge capacity of B3 and B4 are relatively low compared with A1. Figure 2 It can be seen that the cycle stability of A1 is significantly improved compared with B1. The capacity retention rate after 200 cycles at 0.2 A / g is as high as 95%, which is higher than the capacity retention rate of B1 (60%). The capacity retention rates of B3 and B4 after 200 cycles at 0.2 A / g are 86.5 and 88%, respectively, which are significantly lower than A1. Figure 3 The above results show that the atomic layer deposition coated phosphorus-carbon negative electrode material prepared by atomic layer deposition of the present invention has good stability and cycle performance, and solves the volume expansion problem of red phosphorus as a negative electrode material; in addition, after being shelved for 12 months, the first coulombic efficiency, charge specific capacity and cycle performance of the atomic layer deposition coated phosphorus-carbon negative electrode material of the present invention have no obvious decrease, indicating that the Al 2 O 3 The coating layer has a significant insulating effect, which solves the problem of deterioration of the composite material caused by the phosphorus-carbon composite being sensitive to air.
[0073] In summary, the atomic layer deposition coated phosphorus-carbon negative electrode material prepared by atomic layer deposition in the present invention has excellent electrochemical performance, wherein Al 2 O3 Uniformly coated on the surface of the phosphorus-carbon composite, Al 2 O 3 The layer can not only effectively improve the mechanical strength and cycle performance of the phosphorus-carbon composite, but also effectively reduce the sensitivity of the phosphorus-carbon composite to air and increase the storage time of the phosphorus-carbon composite material.
[0074] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. An atomic layer deposition coated phosphorus-carbon negative electrode material, characterized in that: The invention comprises Al2O3, red phosphorus and activated carbon, wherein the red phosphorus is loaded on the surface of the activated carbon, and the Al2O3 is coated on the surface of the red phosphorus.
2. The atomic layer deposition coated phosphorus-carbon negative electrode material according to claim 1, characterized in that: The precursor materials of Al2O3 are trimethylaluminum and water.
3. The atomic layer deposition coated phosphorus-carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the red phosphorus to the activated carbon is (50-45): (50-55).
4. A method for preparing an atomic layer deposition coated phosphorus-carbon negative electrode material, characterized in that: The following steps are involved: S1. Loading red phosphorus on activated carbon to obtain a phosphorus-carbon composite; S2. Loading the coating precursor material onto the phosphorus-carbon composite material by atomic layer deposition to obtain an atomic layer deposition coated phosphorus-carbon composite material.
5. The method for preparing an atomic layer deposition coated phosphorus-carbon negative electrode material according to claim 4, characterized in that: The preparation process of the phosphorus-carbon composite is as follows: red phosphorus and activated carbon are mixed in proportion and then dried to obtain a red phosphorus activated carbon precursor material; the red phosphorus activated carbon precursor material is heated to sublime the red phosphorus, the sublimation temperature is 450-500°C, and then cooled to 200-300°C; the temperature is raised to 350°C again, and finally cooled to obtain the phosphorus-carbon composite.
6. The method for preparing an atomic layer deposition coated phosphorus-carbon negative electrode material according to claim 4, characterized in that: The working temperature of the atomic layer deposition is 200°C, and the temperature of the delivery pipe is maintained at 90°C.
7. Use of the atomic layer deposition coated phosphorus-carbon composite material as described in any one of claims 1 to 3 or the atomic layer deposition coated phosphorus-carbon composite material prepared by the method as described in any one of claims 4 to 6 in the negative electrode of a sodium ion battery.
8. A negative electrode material for a sodium ion battery, characterized in that: The raw material includes the atomic layer deposition coated phosphorus-carbon composite material as described in any one of claims 1 to 3, or includes the atomic layer deposition coated phosphorus-carbon composite material prepared by the method as described in any one of claims 4 to 6.
9. A negative electrode material for a sodium ion battery according to claim 8, characterized in that: The raw materials also include a conductive agent and a binder.